Influence of muscle slack on high-intensity sport performance: A review. - Van Hooren, B.; Bosch, F. (Strength and Conditioning Journal, 2016)
Rapid force development is of paramount importance for most sports. An often overlooked performance limiting factor is muscle slack, which is represented by the delay between muscular contraction and recoil of the series elastic elements. We will review acute and long-term effects of applying cocontractions, countermovements (cms), and external load on muscle slack. Cocontractions may be an effective solution to reduce the degree of muscle slack. Moreover, cms and external load may negatively influence the capability to develop cocontractions and hence may be detrimental to high-intensity sport performance that is usually performed with little or no external load.